Teknik keterampilan mediasi: Analisis komprehensif teknik mediator dalam penyelesaian sengketa - Awaluddin, Ahmad In’am (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
A mediator has a central role as a facilitator in the mediation process, with full authority to direct the course of mediation in order to reach a fair and balanced agreement for the parties to the dispute. Along with the development of the times and the increasing complexity of social problems, the role of mediators has become increasingly challenging. This requires mediators not only to master procedural aspects, but also to have qualified soft skills to support the effectiveness of non-litigation dispute resolution. This research aims to analyze in depth the techniques of skills that are essential for a mediator in carrying out his duties professionally. This research uses a qualitative approach through the library research method, by examining secondary data sourced from various scientific literature, such as books, journals, research reports, theses, and theses. The data obtained were analyzed descriptive-analytically with a systematic approach to comprehensively describe and elaborate the relevant mediation skills techniques. The results of the study show that there are several main techniques that must be possessed by a mediator, including interpersonal communication techniques, active listening, questioning techniques, and reframing techniques. Mastery of these techniques not only increases the effectiveness of the mediation process, but also strengthens the position of the mediator as an adaptive, empathic, and solutive conflict resolution agent in the face of evolving dispute dynamics. Thus, these skills are the main foundation in building trust between parties and creating sustainable equitable solutions.